[PP.16.18] REPRODUCIBILITY OF DIPPING PATTERN AND NOCTURNAL HYPERTENSION IN NORMOTENSIVE AND ESSENTIAL HYPERTENSIVE SUBJECTS. (September 2017) - Lykka, A.; Manousopoulos, K.; Michas, F.; Koroboki, E.; Papageorgiou, C.; Zakopoulos, N.; Manios, E.
Abstract : Objective: It is well known that non-dipping pattern, nocturnal hypertension and isolated nocturnal hypertension are associated with target organ damage development and cardiovascular morbidity and mortality in hypertensive patients. Aim of our study was to evaluate the reproducibility of dipping pattern, nocturnal hypertension and isolated nocturnal hypertension in normotensive and essential hypertensive subjects. Design and method: A total of 68 consecutive never treated individuals referred for evaluation at the Hypertension Unit of our department, underwent 24-h ambulatory blood pressure (BP) monitoring at baseline and 1 month. Subjects with 24-h BP values > = 130/80mmHg were defined as hypertensives, whereas those with 24-h BP <130/80mmHg as normotensives. The degree of nocturnal BP dipping (%) was calculated as 100[1 – nighttime BP/daytime BP] for both systolic and diastolic BP. Dippers were defined as subjects with nocturnal BP fall >10% and non-dippers as patients with nocturnal BP fall <10%. Nocturnal hypertension was defined as nighttime SBP > = 120 mmHg and/or DBP > = 70 mmHg. Isolated nocturnal hypertension Statistical analysis was performed by means of reliability analysis (intraclass correlation coefficient (ICC)) for continuous variables and kappa agreement coefficient for categorical variables. Results: Our study population consisted of 22 normotensives (32%) and 46 hypertensive (68%) subjects. In normotensive subjects the ICC for systolic dipping was 0.172 (p = 0.332) and for diastolic dipping was 0.647 (p = 0.009). The kappa agreement coefficient for systolic non-dippers was 0.273 (p = 0.170), for diastolic non-dippers was 0.507 (p = 0.006), for nocturnal hypertension was 0.560 (p = 0.003) and for isolated nocturnal hypertension was 0.389 (p = 0.068). In hypertensive patients the ICCs for systolic and diastolic dipping were 0.671 (p < 0.001) and 0.557 (p = 0.003), respectively. The kappa agreement coefficient for systolic non-dippers was 0.521 (p < 0.001), for diastolic non-dippers was 0.322 (p = 0.029), for nocturnal hypertension was 0.254 (p = 0.030) and for isolated nocturnal hypertension was 0.237 (p = 0.102). Conclusions: In hypertensive patients, non-dipping pattern is more reproducible than nocturnal hypertension. In contrast, systolic non-dipping pattern is less reproducible than diastolic non-dipping pattern and nocturnal hypertension in normotensive subjects. The reproducibility of isolated nocturnal hypertension is limited.